Probolinggo Regional Regulation No. 8 of 2011 as a legal instrument to encourage the arrangement of street vendors in Probolinggo City Square - Iqbal, Muhammad (Universitas Widya Mataram, 2024)
This research examines how the development and organization of street vendors (PKL) in Probolinggo City Square is facilitated by the Probolinggo Regional Regulation (Perda) Number 8 of 2011. This research aims to assess the effectiveness of this policy in maintaining public order and improving the welfare of traders. Street vendors balance their interests and the wider community's interests. The research methodology used is a qualitative case study, including observation, in-depth interviews with regional government organizations and several street vendors, and analysis of planning documentation. Research findings show that although order and the environment in the Alun-alun area have improved after the implementation of Regional Regulation No. 8 of 2011, several records, such as trader participation and compliance, still need to be improved. There needs to be a strategic plan and policy roadmap to maximize the arrangement of street vendors for public order. This research produced several useful findings as recommendations for the local government so that the implementation of regional regulation No. 8 of 2011 is more optimal. Keywords: Implementation; Regional Regulations; Public Order; Squares; Street Vendors